PEMBERDAYAAN KELOMPOK IBU RUMAH TANGGA DALAM PENGELOLAAN SAMPAH MENJADI PRODUK DAYA JUAL UNTUK MENINGKATKAN PEREKONOMIAN KELURAHAN PANCURAN BAMBU - Kaharuddin Kaharuddin; Rosmita Ambarita; Fauziah Nur Simamora (Universitas Pahlawan Tuanku Tambusai, 2023)
Pancuran Bambu Village is one of four villages in Sibolga Sambas. According to the Sibolga City Central Bureau of Statistics in 2019 the population with an area of ??0.54 km2 is 7711 people with 3893 women and 2818 men. The population is quite high compared to the other three districts. If we pay attention from the environmental aspect, the large population is of course in harmony with the waste that is produced. In this regard, the continuous production of residents' waste if not handled properly will cause environmental pollution. Observations were carried out in environment II of Pancuran Bambu Village, Sibolga Sambas District, to be precise, near coastal settlements where the majority of the population is densely populated with small areas. Based on the results of interviews with the head of environment II, he explained that the environment around him was not very clean, the community did not fully care about environmental cleanliness. Most of the waste is simply thrown into the sea or simply burned. This is supported by minimal cleaning facilities, usually the availability of trash cans on the side of the main road and makes people reluctant to walk far to reach them. The people's only choice is the sea as a practical target for household waste estuaries. Direct observations were also made around the environmental location II of the bamboo shower, the amount of garbage that had accumulated had polluted the environment in the settlement. Keywords: Empowerment, Waste Management, Marketable Products, Improving the Economy